2008
DOI: 10.1074/jbc.m709928200
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation from the Oligomeric State Is the Rate-limiting Step in Fibril Formation by κ-Casein

Abstract: Amyloid fibrils are aggregated and precipitated forms of protein in which the protein exists in highly ordered, long, unbranching threadlike formations that are stable and resistant to degradation by proteases. Fibril formation is an ordered process that typically involves the unfolding of a protein to partially folded states that subsequently interact and aggregate through a nucleation-dependent mechanism. Here we report on studies investigating the molecular basis of the inherent propensity of the milk prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
122
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

7
3

Authors

Journals

citations
Cited by 79 publications
(143 citation statements)
references
References 46 publications
20
122
1
Order By: Relevance
“…Consistent with these data, the fibrilforming region of unstructured κ-casein is in the middle of the protein (Ecroyd et al 2008). Likewise, the crucial fibrilforming residues of amyloid β (Glu11 to Ala21) are in the middle of the peptide (Serpell 2000).…”
Section: The N-and C-terminal Flanking Regions In Shspssupporting
confidence: 74%
“…Consistent with these data, the fibrilforming region of unstructured κ-casein is in the middle of the protein (Ecroyd et al 2008). Likewise, the crucial fibrilforming residues of amyloid β (Glu11 to Ala21) are in the middle of the peptide (Serpell 2000).…”
Section: The N-and C-terminal Flanking Regions In Shspssupporting
confidence: 74%
“…As well, when the rate of α-synuclein fibril formation is increased through the addition of dextran (which acts as a molecular crowding agent), the effectiveness of αB-crystallin as a chaperone decreases [93]. Moreover, we have previously suggested that the intermediate formed during the fibril formation of κ-casein is very short lived compared to other proteins that form fibrils through the typical nucleation-dependent mechanism [109]. This may, at least in part, explain why comparatively high molar ratios of αB-crystallin are required to inhibit fibril formation by κ-casein compared to other systems which have been studied (i.e.…”
Section: Shsps and The Aβ Peptidesmentioning
confidence: 99%
“…However, mechanistic details seem to depend on the stability of the protein aggregates that are formed with the aid of EGCG. Carboxymethylated casein forms fibrils with β-sheet structure that bind to the amyloid dye thioflavin T; it has, therefore, been used as a generic model system for amyloid formation [97]. EGCG inhibits the fibril formation of casein through its binding to a β-sheet-turnsheet motif of the protein [98].…”
Section: Mechanism Of Egcg Interventionmentioning
confidence: 99%